Complementarity of searches for dark matter - Kahlhoefer, F; Felix Kahlhoefer (2014)
The striking evidence for the existence of dark matter in the Universe implies that there is new physics to be discovered beyond the Standard Model. To identify the nature of this dark matter is a key task for modern astroparticle physics, and a large number of experiments pursuing a range of different search strategies have been developed to solve it. The topic of this thesis is the complementarity of these different experiments and the issue of how to combine the information from different searches independently of experimental and theoretical uncertainties. The first part focuses on the direct detection of dark matter scattering in nuclear recoil detectors, with a special emphasis on the impact of the assumed velocity distribution of Galactic dark matter particles. By converting experimental data to variables that make the astrophysical unknowns explicit, different experiments can be compared without implicit assumptions concerning the dark matter halo. We extend this framework to include annual modulation signals and apply it to recent experimental hints for dark matter, showing that the tension between these results and constraints from other experiments is independent of astrophysical uncertainties. We explore possible ways of ameliorating this tension by changing our assumptions on the properties of dark matter interactions. In this context, we propose a new approach for inferring the properties of the dark matter particle, which does not require any assumptions about the structure of the dark matter halo. A particularly interesting option is to study dark matter particles that couple differently to protons and neutrons (so-called isospin-violating dark matter). Such isospin-violation arises naturally in models where the vector mediator is the gauge boson of a new U(1) that mixes with the Standard Model gauge bosons. In the second part, we first discuss the case where both the Z' and the dark matter particle have a mass of a few GeV and then turn to the case where the Z' is significantly heavier. While the former case is most strongly constrained by precision measurements from LEP and B-factories, the latter scenario can be probed with great sensitivity at the LHC using monojet and monophoton searches, as well as searches for resonances in dijet, dilepton and diboson final states. Finally, we study models of dark matter where loop contributions are important for a comparison of LHC searches and direct detection experiments. This is the case for dark matter interactions with Yukawa-like couplings to quarks and for interactions that lead to spin-dependent or momentum suppressed scattering cross sections at tree level. We find that including the contribution from heavy-quark loops can significantly alter the conclusions obtained from a tree-level analysis.